ANALYSIS OF ACTIVITY OF TIJOPAT BANKLAPE IN SECURITY SECURITY - Kenjayev Ilhom Giyozovich (European Science Publishing, 2024)
The article provides an analysis of the activity of commercial banks in the securities market, offers and recommendations on the development of activities of commercial banks in the securities market.
Keywords: Commercial banks, stock market, securities, issuer, investor, financial service, public company, private pension fund.